Reconfiguring National Health System Governance for Non-Military Threats: A Threat-Based Integrated Management Framework for Indonesia - Anton Nugroho; Aris Sarjito; Deni Setiawati; Lusianah Lusianah; Fahrun Fahrun; Oswati Hasanah (Buletin Penelitian Kesehatan, 2026)
Background: Emerging public health crises expose structural vulnerabilities within national health systems, particularly in governance coordination, workforce sustainability, supply chain stability, and digital integration. Indonesia’s COVID-19 experience revealed gaps between regulatory design and operational implementation across these domains. Strengthening governance alignment is therefore essential to enhance preparedness for future systemic shocks. Methods: This study employed systematic document analysis and triangulated synthesis of national regulatory instruments, administrative records, and peer-reviewed studies published between 2019 and 2025. Using iterative cross-domain coding, four analytical domains were examined: crisis governance architecture, workforce resilience, strategic supply chain capacity, and digital health integration. Results: Findings indicate regulatory completeness but operational fragmentation. Temporary dual coordination structures during the pandemic reflected governance misalignment between central and subnational authorities. Persistent psychosocial strain among healthcare workers signals risks to long-term workforce sustainability. Structural dependence on imported pharmaceutical inputs and uneven logistics infrastructure exposed supply chain vulnerabilities. Although digital integration initiatives have progressed, subnational analytic capacity remains uneven. Cross-domain synthesis suggests that institutional alignment gaps, rather than policy absence, constitute the primary systemic challenge. Conclusion: Enhancing Indonesia’s health system resilience requires structural integration across governance, workforce protection, supply chain strategy, and digital capacity. The proposed Integrated Resilience Management Framework offers a policy-oriented pathway to improve institutional coherence and preparedness for future public health crises. This study contributes to health policy scholarship by translating cross-domain structural gaps into actionable system reform strategies.